Study on the X-ray mirror quality specification in advanced light source - Hu, Weishan; Cui, Xiaowen; Li, Ming; Sheng, Weifan; Zhang, Weiwei; Jia, Quanjie; Yang, Fugui (Frontiers in Physics, 2022)
The influence of the X-ray mirror errors on the performance of the beamline increases as the X-ray beam’s coherence improves in advanced light sources. The spatial dispersion of the X-ray beam is crucial for spatial resolution and field of view. However, selecting the appropriate merit function for expressing light distribution and identifying its relationship to optical error is very important in beamline design. We develop a high-efficiency wave-optics simulation platform and a deterministic analysis model to address this issue. The simulation experiments evaluated merit functions, including Strehl ratio, root-mean-square spot size, and encircled energy radius. We proved that the encircled energy radius is a good metric of the x-ray beam spatial dispersion, which matches the results of the Church-Takacs theory. In addition, it is found that limiting the contribution of the low frequency (wavelength>110L) error is effective for specifying the requirements of X-ray mirrors.